2014
DOI: 10.1016/j.jcot.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment of closed total talus dislocation without fracture: A case report and literature review

Abstract: Complete dislocation of the talus not accompanied by a fracture is a very rare injury. Most cases reported are open talus dislocations; closed dislocations are rarely seen. The functional prognosis is poor due to osteonecrosis of the talus which develops in the majority of cases. We present a case of lateral dislocation of the left talus in a 29-year-old road accident victim, but no fracture could be detected in the talus and any of malleolus. Reduction of dislocation had been performed in emergency by externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Previous authors have suggested early total or partial talectomy 5 ; however, subsequent research has shown that such aggressive measures are unneeded. 1 - 3 , 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 The present study chronicles the authors' experience treating a checkrein deformity that resulted from a closed pantalar dislocation. To our knowledge, this study is the first to report such a deformity occurring after this injury.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Previous authors have suggested early total or partial talectomy 5 ; however, subsequent research has shown that such aggressive measures are unneeded. 1 - 3 , 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 The present study chronicles the authors' experience treating a checkrein deformity that resulted from a closed pantalar dislocation. To our knowledge, this study is the first to report such a deformity occurring after this injury.…”
mentioning
confidence: 80%
“…Defined as a pantalar dislocation, total talus dislocation, or enucleated talus, simultaneous dislocation of the talus about all three of its articulations is an extremely rare injury. Pantalar dislocations have been reported to occur in an estimated 2% to 10% of traumatic injuries of the talus 1 , 2 and account for 0.06% of all dislocations. 3 A pantalar dislocation without an open wound is a rare variant, reported to occur in only 15% 4 of cases.…”
mentioning
confidence: 99%
“…The case hereby presented corresponds to a male patient of 23 years old, who after a fall from 15 m during a riot in the prison, he was admitted [1] to the Emergency Service. He showed pain, functional deficit and deformity in the left ankle area.…”
Section: Case Reportmentioning
confidence: 99%
“…Total dislocation of talus is an extremely rare injury [1] . It includes approximately 0,04% of whole human body dislocations and 2% of talus injuries [2] .…”
Section: Introduction (Complications)mentioning
confidence: 99%
“…2 Reduction of the talus usually requires an open technique, although in case reports closed reduction where possible is associated with more favourable outcomes. 1,3,4 Keywords: Orthopaedics, ankle, dislocation…”
mentioning
confidence: 99%